# In need of DESPERATE help

• Apr 12th 2006, 06:07 PM
MIKEJR
In need of DESPERATE help
Can ANYONE please be so helpful as to help me with the following 100 equations.I am clueless about this and I have no idea on how to work out the equations..I would gladly appreciate it.. Please reply just by marking the number with the correct letter. Thanks and God Bless

--------------------------------------------------
Solve

1. (-3ab)^3(2b^2)
A18ab^6
B -18a^3b^5
C -27ab^4
D -54a^3b^5
E54a^3b^5
F 9ab^3

2. (2x^2)^2[(1/2)y^2]^2
Ax^2y^2
B x^4y^2
C(1/2)xy
D(1/4)xy
E x^4y^4
F 2x^2y^4

3. (0.2x^3y^2)^2
A 0.04x^6y^4
B 0.4x^5y^4
C 0.04x^5y^4
D 0.2x^5y^2
E 4xy
F 0.4x^6y^4

4. [(3/10)y^2]^2(10y^2)^2
A (9/10)y^16
B 9y^8
C (3/100)y^16
D3y^4
E 90y^6
F 9y^6

5. [(-1/2)c^2b^3a](2a^2b^2c^4)
A -a^2b^6c^8
B a^4b^6c^8
C -2a^2b^3c^2
D ab^3c^2
E ab^2c^4
F -a^3b^5c^6

6. (18a^5b^5c^10)/(15a^5c^15)

A 3/c^5
B 0
C (6b^5)/(5c^5)
D 1.2(abc^5)
E 6ab^5/5c
F 18b^5c^-5

7.(r^-6s^-2)/[(r^2s^6)^-1]

A r^4s^-4
B 1/(r^4s^4)
C 1/(r^4s)
D r^-8s^-8
E r^8s^8
F s^4/r^4

8. [(r^-4k^2)^2]/[(4k^2)^2]
A 1/(16r^8)
B 4r^-6k^-4
C 1/(8k^4r^2)
D 16r^8k^-4
E 2r^4/k^16
F (1/4)rk^2

9. [(-b^-2c)^0]/(8a^-1c^2)

A 0
B 8ac^2
C (1/8)abc
D a/(8c^2)
E b^2c/8a
F b^2/c^6

10. [(a^5b^2)^2]/[(a^-3b)^2]

A a^22b^2
B a^7b^2
C a^12b
D a^2b
E a^8b^3
F a^16b^2

Express each number in proper scientific notation.

11. (2 * 10^5)(4 * 10^-8)

A 8.0*10^-3 = 0.008
B 5.0*10^12 = 5000000000000
C 0.5*10^-3 = 0.0005
D 8*10^3 = 8000
E 6*10^-3 = -6000
F -2*10^-3 = -0.002

12. (4 * 10^2)(2.5 * 10^6)
A 1.6*10^-4 = .0006
B 6.5*10^4 = 65000
C 1.5*10^4 = 15000
D 10*10^12 = 1000000000000
E 1.6*10^8 = 160000000
F 1.0*10^9 = 1000000000
13.(3.1 * 10^-2)(2.1 * 10^-8)
A 1.48*10^6 = 1480000
B 1.48*10^-6 = 0.00000148
C 1.0*10^-10 = 0.0000000001
D 6.51*10^-10 = 0.000000000651
E 6.51*10^-6 = 0.00000651
F 5.2*10^6 = 5200000

14. (3.1 * 10^5)(1.7 * 10^-3)
A 1.4*10^-2 = 0.014
B 5.27*10^8 = 52700
C 1.82*10^8 = 182000000
D 1.82*10^2 = 182
E 5.27*10^2 = 527
F 4.8*10^-8 = 0.000000048

15.(75 * 10^6)(0.02 * 10^3)
A 0.15*10^3 = 150
B 3.75*10^6 = 375000
C 150*10^7 = 1500000
D 1.5*10^9 = 1500000000
E 1.5*10^3 = 1500
F 3.75*10^1 = 37.5

Which term in each of the following has the lowest degree in x?

16. 5x^2 - 3x^3 + 7 + 2x - a^3x + 8x^6
A 5x^2
B -3x^3
C 2x
D 7
E -a^3x
F 8x^6

Place the following polynomials in the correct descending order in terms of x.

17. 1 + x^3 + x^5 + x^2+ z^3x
A1 + x^2 + z^3x + x^3 + x^5
B x^5 + z^3x + x^3 + x^2 + 1
C 1 + x^5 + x^3 + x^2 + x^3x
D z^3x + 1 + x^2 + x^3 + x^5
E x^5 + x^3 + x^2 + z^3x + 1
F 1 + z^3x + x^2 + x^3 + x^5

18.4x^3y + 3xy^4 - x^2y^3 + y^4 + 7x^4
A 7x^4 + 4x^3y - x^2y^3 + 3xy^4 + y^4
B -x^2y^3 + 3xy^4 + 7x^4 + y^4 + 4x^3y
C 7x^4 + 4x^3y + 3xy^4 + x^2y^3 + y^4
D 7x^4 + y^4 + 4x^3y - x^2y^3 + 3xy^4
E y^4 + 3xy^4 - x^2y^3 + 4x^3y + 7x^4
F 4x^3y + 3xy^4 - x^2y^3 + y^4 + 7x^4

Place the following polynomials in the correct ascending order in terms of a.

19. 11x^2 + 7ax^3 -3xa^4 + 2a^2 - 3a^3x

A 7ax^3 + 11x^2 - 3xa^4 + 2a^2 - 3a^3x
B 11x^2 + 7ax^3 + 2a^2 - 3a^3x - 3xa^4
C 11x^2 + 7ax^3 -3xa^4 - 3a^3x + 2a^2
D 7ax^3 -3xa^4 + 2a^2 - 3a^3x + 11x^2
E -3xa^4 - 3a^3x + 2a^2 + 7ax^3 + 11x^2
F 11x^2 + 2a^2 + 7ax^3 - 3a^3x - 3xa^4

20.7a^3x - 8a^2x^3 + (1/5)x^5 + x^2a^7 + a

A x^2a^7 + 7a^3x - 8a^2x^3 + a + (1/5)x^5<
B a + 7a^3x - 8a^2x^3 + (1/5)x^5 + x^2a^7
C a + 7a^3x - 8a^2x^3 + (1/5)x^5 + x^2a^7
D (1/5)x^5 - 8a^2x^3 + x^2a^7 + a + 7a^3x
E x^2a^7 + a + 7a^3x - 8a^2x^3 + (1/5)x^5
F (1/5)x^5 + a - 8a^2x^3 + 7a^3x + x^2a^7

Find each sum or difference.

21. (17x - 9y) - 11y

A8x - 9y
B17x + 2y
C17x - 20y
D20y - 17x
E17x - 2y
F-3xy
22. (3 - 2a + a^2) - (5 - 8a + a^2)

A2 - 10a + 2a^2
B -6a^2 -8
C -2 - 10a - 2a^2
D 8 + 6a + 2a^2
E 10a - 8
F -2 + 6a

23. (n^2 - 5n + 3) + (2n^2 + 8n -10)
A3n^2 + 3n - 7
B-n^2 - 13n + 13
C3n^2 - 3n + 7
Dn^2 + 3n + 13
E9n - 7
F3n + 7

24. (5ax^2 + 3a^2x - 5x) - (2ax^2 - 5ax + 7x)

A3ax^2 + 8a^2x - 12x
B7ax^2 -2ax + 2x
C3ax^2 + 3a^2x - 5ax + 2x
D3ax^2 + 3a^2x + 5ax - 12x
E5a^2x^2 + 2x
F11a^2x^2 - 12x
25. (x^3 - 3x^2y + 4xy^2 + y^3) - (x^3 - 9xy^2 + 3x^2y + y^3)
A2x^3 - 12xy^2 + 7xy^2 + 2y^3
B6xy^2 + x^2y
C-5xy^2
D13xy^2 - 2y^3
E0
F-6x^2y + 13xy^2

Solve the following equations

26. w(w +12) = w(w + 10) + 4
Aw = 2
Bw = 1/2
Cw = -2
Dw = -1/5
Ew = 5
Fw = 0

27. a(a - 6) + 2a = 3 + a(a - 4)
Aa = 1/3
Ba = 3
Ca = -2
Da = 0
Etrue for all a
Fno solution
28.q(2q - 3) + 20 = 2q(q + 3)
Aq = 0
Bq = 1
Cq = -20/9
Dq = 20/9
Eq = 9/20
Fq = 7

29. x(x + 8) - x(x + 3) - 23 = 3x + 11
Ax = 8
Bx = -6
Cx = 1/2
Dx = 4
Ex = 17
Fno solution

30.y(y - 9) + y(y + 6) + 25 = 2y(y + 10) - 15
Ay = 2/3
By = 15
Cy = -6
Dy = 40/23
Ey = 5/3
Fno solution

Find the product for each of the following (use FOIL).

31.(3x + 4)(2x^2 - 5x + 10)

A6x^3 - 15x + 40
B6x^3 + 23x^2 + 50x + 40
C24x^3 - 60x^2 + 120x
D6x^3 - 7x^2 + 10x + 40
E6x^2 + 7x^2 - 10x + 40
F72x^3

32.(4x + 5)(3x^2 + 8s -9)
A12x^3 + 15x^2 + 32sx _ 45x
B27x^2 + 32s - 9
C12x^3 + 72sx - 45
D12x^2sx
E12x^3 + 32sx - 36x + 15x^2 + 40s - 45
F9x^3 - 16sx + 12

33.(3a + 5)(2a - a^2 + 1)

A-3a^3 + a^2 + 13a + 5
B6a^2 + 13a - 10
C3a^3 - a^2 + 7a + 5
Da^3 - a^2 + 6
E6a^3 + 13a - 5
Fcannot be determined

34. (-2x^2 + 3x - 8)(3x^2 + 7x - 1)

Acannot be determined
B-6x^4 - 5x^3 - x^2 - 59x + 8
C6x^4 + 5x^3 + x^2 + 53x + 8
D-6x^4 + 5x^3 - x^2 + x - 8
E-70x^4
F-6x^2 - 5x + 8

35.(-7b^3 + 2b - 3)(5b^2 - 2b + 2)

Acannot be determined
B35b^5 - 4b^2 - 6
C-35b^5 + 14b^4 - 14b^3 + 15b^2 - 6
D-35b^6 + 16b^4 - 17b^3 + 6
E35b^6 + 14b^5 - 7b^3 + 11b + 9
F-35b^5 + 14b^4 - 4b^3 - 19b^2 + 10b - 6

Find the GCF of the three terms.
.

36. 8b^4, 5c, 3a^2b

A1
B c
C3b
D2a
E2abc
F0

37. 14a^2b^2, 18ab^2, and 20a^3b^4

A4ab
B1
C4b
D6a^2b^2
E7ab
F2ab^2

38. 7y^2 and 14y^2

A7y
By
C2
D7y^2
E14
F1

39. 95x^2 and 304x^8

A x^2
B5x
C17
D19x^2
E19x
F1

40. 220x^3y^2, 55x^2y, and 110xy

A5x
B10y
C5xy
D55xy
E55
Fx^2y^2

Factor each expression. If the expression is in simplest form, please note that it cannot be factored.

41. 36p^2q^2 - 6pq

A p^2q^2(36+6pq)
B pq(36p^2q^2+6)
C -6pq(6pq+1)
D 6pq(6pq-1)
E 6pq(6p^2q^2)
F 6pq(8pq+1)

42. 17a - 51a^3z

A17a(-3a^3z)
B -a(17+51a^3z)
Cz(17a-51a^3)
Da(17-51a^2z)
E17a(1-3a^2z)
F cannot be factored

43. m^3n^2 - 16m^2n^3 + 8mn

Amn(m^2n-16mn^2+8)
B m^2n^2(m-16n_8)
C -mn(m^2n+16m-8)
Dmn(m^3n-16m^2n+8)
E nm(nm^2-16n^2m-8mn)
F 2mn(-m^2n+8mn^2+4)

44. 136xyz - 34wxy

A xy(136z-34w)
B 34xy(4z-w)
C 34(4xyz-wxy)
D 34xy(6z-w)
E 17wxyz(8+2)
F 34xy(w+2z)

45. 28a^2b^2c^2 + 21a^2bc^2 - 7abc

A 7abc(4a^2b^2c^2+3a^2c^2)
B cannot be factored
C 7(4a^2b^2c^2+3a^2bc^2-abc)
D 7a^2b^2c^2(4+3b+1)
E -7abc(4abc+3ac+1)
F 7abc(4abc+3ac-1) br>

Factor each polynomial by grouping.

46. cx + 2c^2x - c - 2c^2

A(cx-c)(2x-1)
B(x_c^2)(1+c)
Cc(1+2c)(x-1)
D(x^2+1)(3c^3)
Ec^2x^2
Fcannot be factored

47. 2x^4 - 5x^2y^2 - 2x^2y^2 + 5y^4

A(5y^2-1)(x^4+y^2)
Bx^4y^4
Cx^2(2x^2-5y^2)-y^2(2x^2-y)
D(x^3+1)(5y^2)
E(x^2-5y^2)(2x+y^2)
F(2x^2-5y^2)(x^2-y^2)

48. 2ax + 6xc + ba + 3bc

A(a+3c)(2x+b)
Bba(cx-ab)
C2x^2(b+c)
D x(2a+6x)+a(b+3c)
E12abcx
F(a-3c)(b+2)

49. 2my + 8x + 8m + 2xy

A2(y+4)(2x-m)
B(x-m)(2y+4)
C2(my+4)+4(2m+xy)
D2(y+4)(m+x)
E8(x+m)+xy
Fcannot be factored

50. a^3 - a^2b + ab^2 - b^3
A(a^2-b)(b+a^2)
B(a+b)(a^2-b^2)
Cab(a-b)
D(b-7a^2)
Ea^2b^2
F(a-b)(a^2+b^2)

51. x^2 - 4xy - 5y^2

A(x-5y)(x+y)
B(x-y)(x+5y)
C(x-5)(y-x)
Dx(x-4y)-5(y)
E(x+5)(x-1)
F (x-5y)(y-x)

52. a^2 + 4ab - 3b^2

A(a-3b)(a-b)
B(a-b)(a+3b)
C(a+b)(a-3b)
D(a+b)(a+3b)
Ea(a+4b)-3(-b)
Fcannot be factored

53. 6m^2 - 32m + 10

A(3m+5)(2m-2)
B (2m-5)(3m-2)
C(6m-5)(m+2)
D 2(3m-1)(m-5)
E (3m-10)(2m-1)
F (3m+10)(2m+5)

54. 15x^2 - 13xy + 2y^2
A (5x-2y)(3x-y)
B (15x+y)(x-2y)
C (x-2y)(15x-y)
D (5x+y)(3x-y)
E (5x-y)(3x-2y
F cannot be factored

55. 9k^2 + 30kn + 25n^2

A (9k+5n)(k+n)
B (3k-5n)(3k+5n)
C (3k-5)(3k-5)
D (3k+5n)^2
E (9k+25)(k+1)
F (9k-5)(9k-5)

Factor each difference of squares.

56. 9x^4y - 16y^3

A (3x^2y-4y)(3x+4)
B y(3x-4)(3x+4)
C y(9x^2-4y)(9x^2+4y)
D y(3x^2-4y)(3x^2+4y)
E y^2(3x^2-4y^2)^2
F cannot be factored

57. -16 + 49x^2

Anot a difference of squares
B (-4-7x)^2
C(-4-7)(4+7x)
D (49x-4)(49x+4)
E (7x-4)(7x+4)
F (7x-4)(-7x+4)

58. (1/64)x^2 - 36z^2

A(x/8-6z)(x/8+6z)
B (x/8-6)(x/8+6)
C (x/4-36z)(x/4+36z)
D (x-6z)64
E (1/8)(x-36)
F cannot be factored

59. (1/4)n^2 - 16
A (n-8)(n+8)
B (n/2+4)(n/2-4)
C (n-2)^2
D (n-2)(n+2)
E (n/4-4)(n/4+4)
F (n-2)^4
• Apr 13th 2006, 01:46 AM
OReilly
What is the meaning of posting a message like this?! I don't think that anyone will reply to this, because its obviously that you don't need help since you haven't even try to solve either one of this 100 equations!
• Apr 13th 2006, 02:20 AM
CaptainBlack
Quote:

Originally Posted by OReilly
I don't think that anyone will reply to this..

Except for us :D

RonL
• Apr 13th 2006, 02:25 AM
CaptainBlack
Quote:

Originally Posted by MIKEJR
Can ANYONE please be so helpful as to help me with the following 100 equations.I am clueless about this and I have no idea on how to work out the equations..I would gladly appreciate it.. Please reply just by marking the number with the correct letter.

by just telling you the right answers.

You may get lucky and someone may explain how to do some of these in
detail.

RonL
• Apr 13th 2006, 02:52 AM
CaptainBlack
Questions 1 thru 10 require you to simplify expressions involving powers or
indicies.

Here the basic things you have to know are:

1. $a^n$ where $n$ is a positive integer means a
multiplied by itself $n$ times.

2. $a^{-n}$ is the same thing as $1/a^n$

3. $a^n a^m=a^{n+m}$, this can be deduced from 1. above

3. $(ab)^n=a^n b^n$, again this can be deduced from 1. above.

===============================================

Now lets try this on:

$
(-3ab)^3(2b^2)=(-3)^3(ab)^3 (2b^2)=-27 (ab)^3 (2b^2)
$

$
=-27\ a^3 b^3 (2b^2)=-27\ a^3 b^3 2 b^2
$

$
=-54\ a^3 b^3 b^2=-54\ a^3 b^5
$

================================================== ==

And another:

$
\frac{18a^5b^5c^{10}}{15a^5c^{15}}=\frac{18}{15}\ \frac{a^5}{a^5} \ b^5\ \frac{c^{10}}{c^{15}}=\frac{18}{15} \ b^5\ \frac{1}{c^{5}}=\frac{6\ b^5}{5\ c^5}
$

This is because:

$
\frac{c^{10}}{c^{15}}=c^{10}\ c^{-15}=c^{10-15}=c^{-5}=\frac{1}{c^5}
$

RonL
• Apr 13th 2006, 02:53 AM
topsquark
Quote:

Originally Posted by CaptainBlack
by just telling you the right answers.

You may get lucky and someone may explain how to do some of these in
detail.

RonL

I'm just impressed by the amount of time used in typing it. :eek:

-Dan
• Apr 13th 2006, 02:54 AM
CaptainBlack
Quote:

Originally Posted by topsquark
I'm just impressed by the amount of time used in typing it. :eek:

-Dan

Cut and paste from a online document?

RonL
• Apr 13th 2006, 03:02 AM
malibupete
That would explain the large spaces in between some of the questions... Though I'm baffled by the fact there's only 59 questions when he said there'd be 100...
• Apr 13th 2006, 03:45 AM
topsquark
Quote:

Originally Posted by MIKEJR
1. (-3ab)^3(2b^2)
A18ab^6
B -18a^3b^5
C -27ab^4
D -54a^3b^5
E54a^3b^5
F 9ab^3

$(-3ab)^3(2b^2)=(-3)^3a^3b^3*2b^2$
$-27*2*a^3b^{3+2}=-54a^3b^5$

The basic rules you need for this (and most of the other problems) are:
$(ab)^n = a^nb^n$
$(a^n)^m=a^{nm}$
$a^na^m=a^{n+m}$

The trick is to break the problem into small steps based on the above formulae. Give some of those problems a try and let us know how it goes.

-Dan

Another useful formula: $a^{-n}=\frac{1}{a^n}$
• Apr 13th 2006, 05:30 AM
CaptainBlack
Quote:

Originally Posted by malibupete
That would explain the large spaces in between some of the questions... Though I'm baffled by the fact there's only 59 questions when he said there'd be 100...

One is base 59 and the other base 100 :D

RonL

(alternative explanation - there were 100 in the original document but he only
copied the first 59, but did not notice).